Essential Oil of Croton ceanothifolius Baill. Potentiates the Effect of Antibiotics against Multiresistant Bacteria - Ana C. J. de Araújo; Priscilla R. Freitas; Cristina Rodrigues dos Santos Barbosa; Débora F. Muniz; Janaína Esmeraldo Rocha; José B. de Araújo Neto; Maria M. C. da Silva; Talysson F. Moura; Raimundo L. S. Pereira; Jaime Ribeiro-Filho; Luiz E. da Silva; Wanderlei do Amaral; et al. (MDPI AG, 2020)
This study is a pioneer in reporting the antibacterial properties of the species Croton ceanothifolius Baill. The genus Croton belongs to the family Euphorbiaceae composed of numerous species with documented biological activities. However, the pharmacological properties of C. ceanothifolius remain poorly understood. The leaves of this plant were submitted to hydrodistillation for essential oil (CcEO) extraction and the phytochemical characterization of the oil was performed by GC/MS. The minimum inhibitory concentration of the CcEO was determined for the evaluation of antibacterial activity against multiresistant strains of Staphylococcus aureus, Pseudomonas aeruginosa, and Escherichia coli. The antibiotic-modulating activity of the oil, in combination with antibiotics, was also evaluated. The combination of the CcEO with penicillin, norfloxacin, and gentamicin presented a synergistic effect. This effect was more significant for the association with antibiotics of the quinolone and aminoglycoside classes against Escherichia coli. The association of oil with gentamicin showed better results with regard to the Gram-positive strain. The association of the oil with norfloxacin against P. aeruginosa also showed synergism, but the association with penicillin did not change the effect of this antibiotic. Thus, it is concluded that C. ceanothifolius essential oil selectively potentiates the action of antibiotics against multiresistant strains.